Financiamento da educação superior e análise de riscos: um estudo com ênfase no programa nacional de assistência estudantil na Universidade Federal da Paraíba - Gajadhar, Ram Anand (2021)
The adoption of risk management by Brazilian public entities is a recent movement coming from the private sector whose purpose is to improve the efficiency of public spending, as it is a tool to assist managers in identifying events capable of providing reasonable certainty regarding reaching the objectives. Thus, this theme was treated at the Federal University of Paraíba, notably within the scope of the National Student Assistance Program (PNAES). The theoretical foundation brings approaches about Public Policy, Higher Education, University Management, Student Assistance Financing, Risk Management, Public Governance and Internal Controls. As a study problem, we sought to analyze how the risks involved in the findings of the audit reports of the General Comptroller of the Union (CGU) and the Internal Audit (AUDIN) of UFPB regarding the granting of student assistance can be managed. This research is characterized as a case study, with descriptive and exploratory objectives and a qualitative approach. The technical procedures used are concentrated around bibliographic and documental analysis. Data were collected and analyzed using the content analysis technique, utilizing the Institutional Development Plan 2019-2023, the Management Reports from 2018-2020 and the audit reports of CGU and AUDIN between 2016 and 2020. The study indicated that the reports of the control organs can serve as a complementary source to the risk management tool, considering that the findings pointed out in them also indicate the existence of risk. It also revealed that execution involves more operational than legal, financial or image risks. The risks, in most cases, are not treated with in an adequate and timely manner due to the absence of mechanisms, causing them to materialize and cause damage to the Program. Thus, as a solution, a panel to monitor the recommendations was proposed in order to control the intrinsic risks in the findings, with managerial indicators that can support the manager responsible for the actions of the PNAES in decision-making that lead to the efficiency of resources and work processes and, in this way, contribute to the unit achieves the objectives it sets itself.